Pyrrolopyrimidines: Design, Synthesis and Antitumor Properties of Novel Tricyclic Pyrrolo [2,3-d]pyrimidine Derivatives - Buer Song; Zarifa Murtazaeva; Lifei Nie; Rustamkhon Kuryazov; Shukhrat Gaybullaev; Chao Niu; Khurshed Bozorov; Haji Akber Aisa; Jiangyu Zhao (Molecules)
The pyrrolo[2,3-d]pyrimidine (7-deazapurine) scaffold is a unique heterocyclic system included in the composition of most nucleotides. In this study, series of the pyrrolo[2,3-d]pyrimidine-imines and 3-halo-substituted pyrrolo[2,3-d]pyrimidines were designed and prepared in high yields. Condensed pyrimidines are obtained via carbonyl-amine condensation and carbon-halogen bond formation. Pyrrolo[2,3-d]pyrimidine-imines containing a bromine substituent at position C-4 of the phenyl ring and azepine side-ring exhibited superior antitumor activity on the colon cancer HT-29 cell line; IC50 values were 4.55 and 4.01 µM, respectively. These results revealed an interesting pattern, where condensed pyrimidinones containing an azepine ring demonstrated selective antitumor activity on the colon cancer cell line HT-29. In addition, the molecular docking results suggest that compound 8g provided a thorough understanding of its interactions with the DDR2 active site. This could pave the way for further development and optimization of DDR-targeting drugs, contributing to advancements in cancer therapeutics. This lead compound may serve as design templates for further studies.